2021
DOI: 10.1167/tvst.10.9.4
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Heads-up Cataract Surgery Using Femtosecond Laser: Efficiency, Efficacy, Safety, and Medical Education—A Randomized Clinical Trial

Abstract: To compare the efficiency, efficacy, and safety, as well as the educational value, of heads-up (three-dimensional visualization system-assisted) and traditional microscopic cataract surgery.Methods: This randomized noninferiority trial enrolled 242 eyes of 201 patients who received femtosecond laser-assisted cataract surgery. The questionnaire study enrolled 26 medical interns and 39 medical students. Patients received surgery under either a three-dimensional visualization system (3D group, 117 eyes) or tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(65 citation statements)
references
References 37 publications
3
61
0
1
Order By: Relevance
“…Finally, a total of 11 studies of 11 articles (8842 eyes) met the inclusion and exclusion criteria and were included in the systematic review and meta-analysis. Notably, nine studies were included in the meta-analysis of postoperative BCVA [ 4 , 5 , 6 , 8 , 9 , 10 , 11 , 12 , 14 ] and mean surgical time duration [ 4 , 5 , 7 , 8 , 9 , 11 , 12 , 13 , 14 ], and only five studies were included in the meta-analysis of the incidence rate of intraoperative complications [ 5 , 7 , 9 , 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a total of 11 studies of 11 articles (8842 eyes) met the inclusion and exclusion criteria and were included in the systematic review and meta-analysis. Notably, nine studies were included in the meta-analysis of postoperative BCVA [ 4 , 5 , 6 , 8 , 9 , 10 , 11 , 12 , 14 ] and mean surgical time duration [ 4 , 5 , 7 , 8 , 9 , 11 , 12 , 13 , 14 ], and only five studies were included in the meta-analysis of the incidence rate of intraoperative complications [ 5 , 7 , 9 , 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 3D HUVS offers better ergonomics (the surgeon does not need to bend the neck to look into the microscope eyepieces) and better visualization (high-resolution surgical field visualization with better magnification). Furthermore, 3D imaging is beneficial for teaching, as everyone in the operating room can see the same high-resolution view that the surgeon observes on the screen [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. However, some studies reported different 3D HUVS drawbacks, such as a possible longer surgical time, a challenging learning curve, and a higher surgical workload [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 28 Actually, researches on cataract surgery have not ceased in the past decades in the pursuit of better results. [29][30][31] Therefore, studies are in emergent need to verify whether updates in the surgical systems do lead to better outcomes. The Open access active-fluidics system has been put into use for many years, but it is not yet widespread.…”
Section: Discussionmentioning
confidence: 99%
“…The vision loss caused by cataract is a huge burden on society and families; fortunately, it is curable 2 28. Actually, researches on cataract surgery have not ceased in the past decades in the pursuit of better results 29–31. Therefore, studies are in emergent need to verify whether updates in the surgical systems do lead to better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Three previously published articles have described no difference in the total surgical time between the 3D system and BM [ 3 , 17 , 23 ]. However, one study reported that the duration of cataract surgery was 5 min shorter with the use of the 3D surgical system [ 24 ].…”
Section: Discussionmentioning
confidence: 99%